Evaluation of Internal Quality Management Building a Child-Friendly School (SRA) at SMKN 1 Sangatta Utara - Sukamti, Sukamti; Piandani, Darus Winanten; Pratomo, Danu; Azainil, Azainil; Komariyah, Laili (Jurnal Riset Ilmu Pendidikan, 2025)
Child-Friendly Schools (SRA) as regulated in PPPA Regulation No. 12 of 2022 aims to make schools a safe place and support children's development. This study aims to evaluate internal quality management in building SRA at SMKN 1 Sangatta Utara. The study used a descriptive method with a qualitative approach, data collection techniques through in-depth interviews, observations, and document studies, as well as data analysis using the Miles and Huberman model. The results of the study indicate that planning has not been determined in writing through a Decree on the Determination of SRA, but a Violence Prevention and Handling Team (TPPK) has been formed. Organization is still divided between TPPK and the Student Affairs Team. Implementation has not involved all teachers and education personnel. Supervision is less than optimal because it is only carried out by the principal. Supporting factors include the existence of the TPPK and Student Affairs Team programs and the allocation of funds in the RKAS. Inhibiting factors include the absence of a Decree on the Determination of SRA, lack of understanding of all school residents, incomplete facilities and infrastructure, and the absence of special training related to SRA.